IMPLEMENTASI KEBIJAKAN PENGAWASAN DAN PENGENDALIAN PENJUALAN MINUMAN BERALKOHOL DI KABUPATEN MUARA ENIM PROVINSI SUMATERA SELATAN - Rachmansyah Saputra (Fakultas Politik Pemerintahan IPDN, 2019)
Implementation of Policy for Supervision and Control of Sales of Alcoholic Beverages in Muara Enim Regency, South Sumatra Province. This study aims to determine and analyze the implementation, inhibiting factors and appropriate strategies in the policy of monitoring and controlling the sale of alcoholic beverages. The research method used in this study is descriptive with a qualitative approach. Data obtained through observation, interview, documentation and triangulation techniques. The results of the study indicate that the implementation of the policy of monitoring and controlling the sale of alcoholic beverages in Muara Enim Regency has not gone well. This is seen based on several performance indicators, among others: not yet well implemented Regional Regulation No. 4 of 2005, the lack of quality human resources and limited budgets, and related interagency communications that have not been implemented properly. Keywords: implementation, supervision, control, policies